2004
DOI: 10.2460/ajvr.2004.65.188
|View full text |Cite
|
Sign up to set email alerts
|

Determination of passive mechanical properties of the superficial and deep digital flexor muscle-ligament-tendon complexes in the forelimbs of horses

Abstract: Both the muscle-tendon and ligament-tendon portions of SDF and DDF myotendinous complexes had important roles in supporting the forelimb of horses. Although muscle tension can be enhanced by elbow joint flexion and active contraction, the accessory ligaments transmitted more force to the distal tendons than did the muscles under the conditions tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…The ligaments were represented as passive elastic structures. The force-length curve of each tendon and ligament was modeled by fitting a third-order polynomial function to experimental data reported in the literature (Jansen et al, 1993a;Jansen et al, 1998;Kostyuk et al, 2004;Lochner et al, 1980;Meershoek et al, 2001;Swanstrom et al, 2004;Swanstrom et al, 2005a;Swanstrom et al, 2005b;Weller, 2006). The lengths, moment arms and tendon wrapping directions of each muscle and ligament were calculated using a software program called OpenSim (Delp et al, 2007).…”
Section: Musculoskeletal Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligaments were represented as passive elastic structures. The force-length curve of each tendon and ligament was modeled by fitting a third-order polynomial function to experimental data reported in the literature (Jansen et al, 1993a;Jansen et al, 1998;Kostyuk et al, 2004;Lochner et al, 1980;Meershoek et al, 2001;Swanstrom et al, 2004;Swanstrom et al, 2005a;Swanstrom et al, 2005b;Weller, 2006). The lengths, moment arms and tendon wrapping directions of each muscle and ligament were calculated using a software program called OpenSim (Delp et al, 2007).…”
Section: Musculoskeletal Modelingmentioning
confidence: 99%
“…Most notably, the two digital flexor muscle-tendon units have accessory ligaments (ALs) that generate forces in addition to the forces developed by the muscle-tendon units alone (Swanstrom et al, 2004). These ligaments insert near to the musculotendinous junction and connect the tendon to the palmar aspect of the carpus (from the DDF) or the caudal radius (from the SDF).…”
Section: Introductionmentioning
confidence: 99%
“…Loading of the passive structures of the distal forelimb has been the subject of frequent study (Biewener, 1998;Harrison et al, 2010;Jansen et al, 1993;Meershoek et al, 2001;Swanstrom et al, 2004;Swanstrom et al, 2005;Wilson et al, 2001); however, little is known about the coordination of active muscle contraction (Butcher et al, 2009;Hoyt et al, 2005;Jansen et al, 1992;Tokuriki et al, 1989). Muscle activation patterns have been predicted from calculations of net joint torques using biomechanical models of the forelimb (Harrison et al, 2010;Swanstrom et al, 2005;Wilson et al, 2001), but no study has validated these calculations against direct measurements obtained in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…2001). Swanstrom et al . (2004) demonstrated that the SDF muscle‐tendon complex has a relatively small active force component, suggesting a primary function in storing energy during loading.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the SDF muscles to maintain a forceful contraction over a range of muscle fibre lengthening and shortening and properties of the collagen fibrils within the tendon, may influence the degree of strain placed on the SDF muscle and tendon during the stance phase (Zajac 1989; Brown et al . 2003; Swanstrom et al . 2004).…”
Section: Introductionmentioning
confidence: 99%